PENGARUH ANGGARAN PARIWISATA TERHADAP PRODUK DOMESTIK BRUTO, TENAGA KERJA, DAN DEVISA PARIWISATA - Ollani Vabiola Bangun; Savitri Wulandari; Eko Ananto; Iranisa (Jurnal Budget : Isu dan Masalah Keuangan Negara, 2023)
Although the tourism budget is the lowest compared to other national functional expenditures, it is expected to have a positive effect on the national economy and destination areas. The contribution can be reflected in GDP, foreign exchange of tourism, and employment. To find out how big the effect is, this paper aims to analyze the effect of the tourism budget on the national economy. This research uses quantitative methods with regression models. The results showed that the tourism sector budget has had positive and significant implications for tourism GDP, foreign exchange of tourism, and labor in the tourism sector. Every increase in the tourism sector budget of Rp 1 billion is estimated to generate a GDP of Rp355,005.30 billion and foreign exchange of USD751.12 and increase the number of workers by 543 people. Therefore, it is suggested that the government increase the tourism sector budget allocation so that the tourism sector can make a greater contribution to national economic growth.